Identification and characterization of epitopes on the merozoite surface protein-??? (Msp-142) of plasmodium knowlesi / Cheong Fei Wen - Cheong, Fei Wen (2014)
Malaria is one of the infections that causes high global mortality and morbidity annually. Plasmodium knowlesi has been recognised as the fifth human Plasmodium species that can cause human malaria and it can be potentially life threatening. The merozoite surface protein 1 (MSP-1) undergoes two proteolytic steps during maturation of merozoites and invasion of merozoites into erythrocytes. During the first process, the MSP-1 precursor polypeptide is cleaved into four major fragments including MSP-142. The secondary process further cleaves the MSP-142 into two fragments, MSP-133 and MSP-119. In the present study, the ~28 kDa recombinant protein MSP-133 and ~42 kDa recombinant protein MSP-142 of P. knowlesi (pkMSP-133 and pkMSP-142 respectively) were expressed using Escherichia coli system. The purified proteins were evaluated with malaria and non-malaria human patient sera using Western Blot and ELISA assays. In the Western Blot assays, pkMSP-133 showed sensitivity of 98.3% and specificity of 97.4% in detecting malaria antibodies. In ELISA, the sensitivity for pkMSP-133 was 76.3%, with the specificity 94.9%. The pkMSP-142 had a sensitivity of 91.0% for detection of human malaria in both assays. Specificity of pkMSP-142 was 97.5% and 92.6% in Western blots and ELISA, respectively. High sensitivity and specificity of pkMSP-133 and pkMSP-142 in immunoassays reveals that these two recombinant proteins could be useful in general sero-epidemiological screening. Sensitivity and specificity obtained for pkMSP-142 in Western Blot and ELISA assays were consistently higher (>90%) as compared to pkMSP-133 which had lower sensitivity in ELISA (<80%). Besides, the MSP-142, which is made up of the MSP-133 and MSP-119 regions, has immunodominant T cell and B cell epitopes. Hence, this study aimed to evaluate the immunogenicity of pkMSP-142 using mouse model and to identify iv the potential epitopes. Mice immunized with pkMSP-142 had increased levels of cytokine interferon-gamma, interleukin-2, interleukin-4, and interleukin-10 significantly as compared to the levels in negative control mice. Furthermore, the endpoint titres of pkMSP-142-raised antibody were high, with the following IgG isotype distribution: IgG1 > IgG2b > IgG3 > IgG2a. Potential epitopes on P. knowlesi MSP-142 were identified using synthetic peptide library and phage display library approaches. In these approaches, pkMSP-142- immunized mice sera were used for screening of the potential epitopes. Nine potential epitopes were identified using synthetic peptide library, and 14 using the phage display library. Two regions (residues 37-95 and residues 240-289) were identified to be the potential dominant epitope regions. Two peptides from the peptide library, P10 (TAKDGMEYYNKMGELYKQ) and P31 (RCLLGFKEVGGKCVPASI), were selected and evaluated using mouse model. P10 and P31-immunized mice sera reacted with recombinant P. knowlesi MSP-142, and the IgG isotype distribution was IgG2b > IgG1 > IgG2a > IgG3. Antibodies raised against P10 and P31 recognised P. knowlesi blood stage parasites, indicating that both peptides were immunogenic and might correspond to the epitopes that serve as the binding sites for antibodies on the parasites. Furthermore, interferon-gamma and interleukin-2 levels were significantly higher in P31-immunized mice. With further evaluations, P10 and P31 can potentially be used in the development of malaria vaccine and therapeutic agents